A case study on lightning protection system in term of collection volume method at UiTM Shah Alam Canseleri Building / Muhammad Rauf Roslan - Roslan, Muhammad Rauf (2013)
This paper presents about the study on lightning protection system at UiTM Shah Alam Canseleri building. The existing lightning protection are exist at the building since 2006.The air terminals that been used is Dynasphere Controlled Leader Triggering (CLT).The method that been used will determined based on Eritech Lightning Protection Standard. Besides, the risk of the building will be determined based on Malaysia Standard Protection MS 62306.